To find \((f-g)(t)\), we need to subtract the cost function \(g(t)\) from the net income function \(f(t)\).
We have:
- \(f(t) = -0.05t^3 + 1.51t^2 - 11.12t + 50.71\)
- \(g(t) = 0.04t^3 + 1.23t^2 - 8.57t + 31.43\)
Now, we can compute \((f-g)(t)\):
\[ (f-g)(t) = f(t) - g(t) \] \[ = \left(-0.05t^3 + 1.51t^2 - 11.12t + 50.71\right) - \left(0.04t^3 + 1.23t^2 - 8.57t + 31.43\right) \]
Distributing the negative sign, we get:
\[ = -0.05t^3 + 1.51t^2 - 11.12t + 50.71 - 0.04t^3 - 1.23t^2 + 8.57t - 31.43 \]
Now, we can combine like terms:
-
Cubic terms: \(-0.05t^3 - 0.04t^3 = -0.09t^3\)
-
Quadratic terms: \(1.51t^2 - 1.23t^2 = 0.28t^2\)
-
Linear terms: \(-11.12t + 8.57t = -2.55t\)
-
Constant terms: \(50.71 - 31.43 = 19.28\)
Putting it all together, we have:
\[ (f-g)(t) = -0.09t^3 + 0.28t^2 - 2.55t + 19.28 \]
Interpretation:
The function \((f-g)(t)\) represents the company's profit, measured in thousands of dollars. More specifically:
- If \((f-g)(t) > 0\), the company is making a profit in year \(t\) (since net income exceeds costs).
- If \((f-g)(t) < 0\), the company is incurring a loss in year \(t\) (since costs exceed net income).
- If \((f-g)(t) = 0\), the company breaks even, meaning its revenues are equal to its costs.
In summary, \((f-g)(t)\) provides insights into the company's profitability over the years from 2000 to 2020.